Artistic swimming and school engagement: the mediating role of metacognition and technology - Merlo, Gianluca; Jaforte, Luna (Frontiers in Education, 2024)
This article presents a cross-sectional study that explores the association between artistic swimming and school engagement in a sample of 500 Italian adolescents. The study aimed to examine whether the practice of artistic swimming would foster strategic metacognitive skills. These skills, in turn, were hypothesized to positively influence school engagement and reduce recreational technology use, which could pose a risk to school engagement. The findings revealed that the relationship between artistic swimming and scholastic engagement, encompassing both cognitive and behavioral aspects, was entirely mediated by metacognitive strategies and reduced recreational technology usage. Moreover, students engaged in artistic swimming exhibited significantly higher levels of metacognitive strategies and scholastic engagement compared to their counterparts involved in other sports. The article also addresses the limitations inherent in the cross-sectional design and suggests potential avenues for future research.